Magnesium metallic glass : processing and characterisation - Ang, Jia Liang (2010)
Bulk metallic glasses have created a huge area of interest for researchers around the world ever since the invention of the metallic glass. Many different metal based metallic glasses are currently researched on for commercial and scientific applications. In this report, magnesium based metallic glass has been studied due to its excellent specific strength and low cost. The main objective of the project is to investigate the most suitable operating techniques and conditions which can be used to produce the magnesium glass. Two main types of process were used namely, casting and melt spinning. Each process operates with a different approach and the product varies from each other although the composition of the starting material is similar. This difference in the final result proves the significance of the steps in the individual process. Finally, it was concluded that melt spinning was the more suitable process as it had better environmental controls than casting. The method in melt spinning was able to produce a more superior specimen than casting. For the 2 casting processes, raw material casting process did not produce any amorphous structure while pre alloy casting was able to achieve a good percentage of amorphous structure in the sample. Further improvements to the existing techniques include taking the best out of the 2 methods to achieve the objectives. By merging melt spinning and casting together, the desired metallic glasses that melt spinning is able to achieve easily can be obtained, and larger samples can also be produced to different shapes and sizes by replacing the spinning wheels to the moulds from casting. In this way, the disadvantages from each method can be compensated by the benefits of the other method thus creating metallic glasses of enhanced qualities.